Comparison of parenting styles, loneliness and communication skills in homeless and normal women - Siaha, Ali; Banisi, Parinaz; Mohammadiariya, Alireza (Applied Family Therapy Journal (AFTJ), 2021)
Objective: Women heads of households are considered as vulnerable groups in society due to problems in parenting. The aim of this study was to compare parenting styles, loneliness and communication skills in homeless and normal women.Method: The statistical population of this study included all female-headed households who referred to Sarai Mahalla in Tehran, whose number was equal to 360 people and the approximate number of sample size, according to the size of the population and referring to Krejcie and Morgan table, is equal to 186 N was estimated. Data collection tools included Bamrind (1991) Parenting Beck Questionnaire, Jarabek Communication Skills Questionnaire (2004) and Russell, Pilva and Cortona (1980) Loneliness Questionnaire. Data analysis method was used through descriptive statistics of frequency, frequency percentage, frequency distribution table, drawing diagrams and describing the characteristics of respondents to the questionnaire and through inferential statistics of Kolmogorov-Smirnov test to determine the normality of research variables and also to analyze Data In this study, according to the type of information and objectives, independent t-test was used to confirm or reject the questions. Data analysis was performed by SPSS 24 software.Results: The results showed that there was a significant difference between loneliness and communication skills in homeless and normal women. In other words, normal women scored higher in the communication skills variable and homeless women scored higher in the loneliness variable, and this difference is significant. Due to the size of the effect, there is little difference in communication skills. The results also showed that there is a significant difference between parenting styles in homeless and normal women. In other words, normal women scored higher in the parenting style variable, and this difference is significant.